It's a relatively simple first-degree equation in 'x'.
The solution can be found like this:
0.25x + 1.3 = 4x + 2
Subtract 0.25x from each side:
1.3 = 3.75x + 2
Subtract 2 from each side:
-0.7 = 3.75x
Divide each side by 3.75 :
x = -0.7 / 3.75 = -0.1867 (rounded)
x=.293 y=11.328
(3x - 4)(4x - 3)
X + 4(x) + 2x+ 4x + 25x + 2
x = 1 and y = 6 so the lines intersect at the point (1, 6)
2
3X - 23 + 4X + 6 = 5X + 8combining like terms, 7X - 17 = 5X + 8subtracting 5X and adding 17 to each side, 7X - 5X = 8 + 17Then, 2X = 25X = 12.5
4x-14
The answer to the problem of 13 equals -4x plus 9 is x equals -1.
4x plus 7 plus 3x equals 19 plus xx = 2
(9,3)
4x+32=-4x+16x4x+32=12x-4x -4x32=8x/8 /84=x
-4x + 4y = 1